Access to pocket money and low educational performance predict tobacco use among adolescent boys in Kerala, India - Sailesh Mohan, M.D., M.P.H., P. Sankara Sarma, Ph.D., K.R. Thankappan (Preventive Medicine 41 (2005) 685 - 692, 2005)
Tobacco use is increasing among adolescents. We conducted this study to find prevalence and correlates of tobacco use among adolescent boys in Trivandrum city, Kerala. Using a two-stage cluster sampling technique, 1323 boys (12-19 years) were selected from 14 schools. Information on tobacco use, academic performance, pocket money, and other variables was collected using a questionnaire. Multivariate analyses were done to find associations between current use of tobacco and other variables. Prevalence of current tobacco use was 11.3